Primordial black hole dark matter evaporating on the neutrino floor - Roberta Calabrese; Damiano F.G. Fiorillo; Gennaro Miele; Stefano Morisi; Antonio Palazzo (Physics Letters B, 2022)
Primordial black holes (PBHs) hypothetically generated in the first instants of life of the Universe are potential dark matter (DM) candidates. Focusing on PBHs masses in the range [5×1014−5×1015] g, we point out that the neutrinos emitted by PBHs evaporation can interact through the coherent elastic neutrino nucleus scattering (CEνNS) producing an observable signal in multi-ton DM direct detection experiments. We show that with the high exposures envisaged for the next-generation facilities, it will be possible to set bounds on the fraction of DM composed by PBHs improving the existing neutrino limits obtained with Super-Kamiokande. We also quantify to what extent a signal originating from a small fraction of DM in the form of PBHs would modify the so-called “neutrino floor”, the well-known barrier towards detection of weakly interacting massive particles (WIMPs) as the dominant DM component.